PERAN KI SUWADI DALAM PERKEMBANGAN WAYANG KULIT JAWA TIMURAN GAGRAG TROWULANAN DI KABUPATEN JOMBANG - Bagus Mustiko Aji; Tatik Harpawati (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
The tittle of this research is â€œThe Role of Ki Suwadi on Develop East Java Leather Puppet GagragTrowulanan on Jombang regencyâ€ such as research focus of social construction study and the function structural. This research questions was formulated as follows: (1) how is the universal conception the instrumental of gagragTrowulan(2) How to Ki Suwadi safe and develop east java leatherpuppet gagragTrowulan. This Research method that use in this research is qualitative research, and the data validity used triangulation data that is data research use three methods, that is legwork with observation, interview, literature review and transcription from source audio-visual.The result of this research is the process of Ki Suwadi from â€œnyantrikâ€ for senior mastermind gagragTrowulanis Ki Pit Asmoro. Ki Suwadi very take effect for the development of East Java leather puppet gagragTrowulan until now. His pakeliran get a good respond from the society, be evidenced a lot of young mastermind who doing nyantrikactivity to him. All of The students of Ki Suwadi become a mastermind. They are become a famous mastermind in his area. That is become a continuity East Java leather puppet gagragTrowulan until now (2018).Keywords : leather puppet show, Gagrag Trowulanan, The Role of Ki Suwadi, cantrik.